Evaluation of the role of pre-operative albumin and its post-operative drop in the prediction of outcomes of emergency laparotomy - Kumar, Devaprashanth Mohan; Sivakumar, Sindhu (International Surgery Journal, 2020)
Background: Laparotomies are commonly performed surgeries in an emergency setting. The complications associated with these are a result of the activation of the surgical stress response, the magnitude and duration of which are proportional to the surgical injury. Albumin is an important negative phase reactant. This study was an attempt to evaluate the effectiveness of measurement of pre-operative albumin and the post-operative drop in albumin levels in the prediction of post-operative morbidity and mortality following laparotomy. Methods: Albumin levels of 50 patients undergoing emergency exploratory laparotomy in Victoria Hospital were measured pre and post operatively. The percentage drop in albumin levels was noted. The outcomes were noted and classified according to Clavein Dindo Classification. Unpaired t-test and ANOVA test was used for statistical analysis. A p value of <0.05 was considered statistically significant. Results: 62% of the patients had hypoalbuminemia preoperatively. 58% of patients had post-operative complications. The mean preoperative albumin levels for patients without complications was 3.83 while that for patients with complications was 2.78 (p<0.05). The mean percentage drop in albumin values was 9.66% for patients without complications while it ranged from 14.79 (Clavein Dindo 1) - 24.27 (Clavein Dindo 5) for patients with complications (p=0.047). A negative correlation was noted between the preoperative albumin values and the duration of hospital stay while the drop in albumin levels showed a positive correlation with the duration of hospital stay. Conclusions: Measurement of albumin levels pre-operatively and in the immediate post-operative period following laparotomy can prove as a useful tool and an early indicator of morbidity and mortality following laparotomy.